Pengaruh karakteristik perusahaan, rasio keuangan, corporate tax rate dan non-debt tax shield terhadap kebijakan hutang pada perusahaan food and beverages - STEVEN YAP (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
The purpose of this research is to test and analyze empirically the influence of growth, tangibility, firm size, business risk, liquidity, profitability, corporate tax rate, and non-debt tax shield toward debt policy. This study was also to compare result of the previous research within the research. Sample of this research is food and beverages sector companies that listed in Indonesia Stock Exchange for period 2005-2013. The purposive sampling is used as sampling technique, where 7 companies met the criteria and were analyzed using descriptive statistics and panel data regressions with fixed effect model to test the hypothesis. The result of this research shows that growth, tangibility, firm size, liquidity, profitability and non-debt tax shield does influence debt policy, while business risk and corporate tax rate do not influence debt policy.